(untitled) (Communications in Computational Physics, 2018)
There exist many spatial discretization schemes that are well able to provide accurate and stable approximations for isothermal turbulent flows. Comparatively little analysis has been made of the performance of these schemes in the presence of temperature gradients driven by combustion. In this paper, the effects of temperature gradients on numerical stability are explored. A surprising result is that temperature gradients in the flow have a tendency to impinge on left half plane (LHP) stability of the spatial discretization scheme. Reasons for this tendency are explored and two remedies are proposed: one based on the particular class of finite difference schemes, and one based on an alternative method of boundary condition specification.